Type of Exercise Affected to Testosterone Level on Female Athletes: A Systematic Review - Prasana, I GEJ; Negara, Anak AGAP (Universitas Kristen Maranatha, 2025)
Testosterone is a hormone that plays an important role in stimulating muscle development and regulating fat metabolism.While exercise influences testosterone levels, females generally experience smaller increases in testosterone levels after exercise than males. This has led some female athletes to misuse testosterone, posing potential health risks and altering physiological functions. This systematic review aims to examine the effects of different exercise modalities on testosterone levels in female athletes, providing insights into optimal training approaches. A comprehensive literature search was conducted using PubMed, Google Scholar, Medline, and PEDro, with keywords including